Features of processes of globalization are in Kazakhstan (Journal of Philosophy Culture and Political Science, 2015)
In this article an author marks that at the end of XX age a few youngstates appeared in a geographical environment, and, including RepublicKazakhstan. Priority direction for the independent young state was enteringinto a world economic contest and maintainance of stable politicaldevelopment. In this direction of RK analysing social, cultural, political andeconomic possibilities gives an original estimation a worldwide policy.Including, in RK conducts a review.
Keywords: ethnicity; nationality; civilization; globalization.